Comparison of the Legal Systems of Indonesia and Singapore Regarding the Industrial Relations Dispute Settlement Process - Pravana, Alam; Ratnawati, Elfrida (Syntax Corporation Indonesia, 2024)
This study aims to identify, understand, and analyse a comparison of the legal systems of Indonesia and Singapore regarding the industrial relations dispute settlement process. Indonesia is one of the countries that adheres to the civil law legal system, while Singapore adheres to the common law legal system. There are similarities as well as differences in the legal system in the process of resolving industrial relations disputes between Indonesia and Singapore. Elements of the societal changes that have occurred have affected Malay law and legal politics because there have been changes in the social structure and political dynamics, moreover, there are many descendants of Chinese in Singapore. This study uses a normative legal method with a comparative legal approach. The results of this study show that the industrial relations settlement process in Indonesia begins with bipartite negotiations, tripartite (mediation, conciliation, arbitration), and through industrial relations courts, while in Singapore it begins with collective bargaining or negotiation (collective bargaining), tripartite (conciliation or mediation), and through an arbitration institution (the Industrial Arbitration Court). In his book, Peter de Cruz related to labor law that the main comparative objective is to discover how the legal system is with different historical and cultural backgrounds. In terms of similarities, both Indonesia and Singapore put forward an initial negotiation in the form of deliberations or negotiations, while the difference that can be analysed is that the process of resolving industrial relations disputes in Singapore is relatively faster than in Indonesia. This is also influenced by the elements of societal change that have affected Malay law and legal politics because there have been changes in political dynamics, especially with the large number of Chinese descendants in Singapore. The process of resolving industrial relations disputes, which takes a long time and is complex in nature, requires an update that aims to be more efficient and faster.